2020
DOI: 10.4081/aiua.2020.1.50
|View full text |Cite
|
Sign up to set email alerts
|

Papillary vs non-papillary access during percutaneous nephrolithotomy: Retrospective, match-paired case-control study

Abstract: Objective: The most crucial steps of percutaneous nephrolithotomy (PCNL) are the percutaneous access and dilation of the access route. Recent literature suggests that papillary access to renal calyx is the accepted method. Despite this rule, we do not always make papillary puncture and we puncture wherever we can to achieve stone-free status and reduce unnecessary access. In this study, we present our results with papillary vs non-papillary access in patients with a kidney stone. Material and methods: Two hund… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 7 publications
1
4
0
Order By: Relevance
“…In contrast, the operative time was significantly shorter in the non-papillary arm. 5 Similar to their results, no statistically significant differences were reported in a retrospective matched-pair case-control study by Tahra et al 6 Out of 69 patients with non-papillary puncture, a blood transfusion was only required in one patient. No significant differences were reported for overall complications.…”
Section: Authorssupporting
confidence: 74%
“…In contrast, the operative time was significantly shorter in the non-papillary arm. 5 Similar to their results, no statistically significant differences were reported in a retrospective matched-pair case-control study by Tahra et al 6 Out of 69 patients with non-papillary puncture, a blood transfusion was only required in one patient. No significant differences were reported for overall complications.…”
Section: Authorssupporting
confidence: 74%
“…Operation time, SFR and length of hospital stay (LOS) were similar between the groups. There were no significant differences concerning overall complication rate, drop in haematocrit level and transfusion rate [9]. As a conclusion, the surgeon must make a personalized decision case by case.…”
Section: Papillary Versus Non-papillary Puncturementioning
confidence: 73%
“…[ [20] , [21] , [22] ] reporting a significantly higher risk of vessel injury when a non-fornical puncture was undertaken. Nevertheless, the clinical studies on non-papillary punctures have demonstrated their comparable safety and efficiency for standard and mini-PCNL including complex renal stones with multiple PCNL tracts [ [23] , [24] , [25] , [26] ].…”
Section: Discussionmentioning
confidence: 99%